Development of a new water ecological health assessment method for small river in Shanghai, China - Houtao Xu (IWA Publishing, 2021)
Seventeen indices were selected to structure a new water ecological health assessment system, consisting of water quality, ecological system, and ecological landscape, for evaluation of small rivers in Shanghai, China. There are 200 samples taken from 56 rivers distributed in ten districts from 2014 to 2015 in Shanghai, which were selected to constitute the study case, and the mean value of each indicator was used in the evaluation. According to various features, including natural geographical condition, social development level, etc., these rivers were classified as one of three types: central urbanization watercourse (CW), new town watercourse (NW), and village watercourse (VW). The results showed that the investigated rivers were at a medium health level, ranging from 1.79 to 3.59, with the average being 2.95. The ecological health of streams in rural areas is better than that of CW rivers and NW rivers. This study is expected to provide accurate statistics and appraisal for the improvement of river health.